Laparoscopic surgery in urological oncology: brief overview - Colombo Jr,Jose R. (2006)
The authors report the experience of a high-volume center with laparoscopic surgery in urological oncology, as well as a review of other relevant series. Laparoscopic outcomes in the treatment of adrenal, kidney, upper tract transitional cell carcinoma, bladder, prostate, and testicular malignancy are described in this review. Specific considerations as complications and port-site recurrence are also addressed. The authors concluded that the intermediate-term oncological data is encouraging and comparable to open surgery.